Chronic pain in the time of COVID‐19: Stress aftermath and central sensitization. Issue 2 (25th October 2020) - Serrano‐Ibáñez, Elena R.; Esteve, Rosa; Ramírez‐Maestre, Carmen; Ruiz‐Párraga, Gema T.; López‐Martínez, Alicia E.
Abstract : Objectives: The COVID‐19 crisis is a significant stressor worldwide. The physical and emotional condition of individuals with pain sensitization syndromes who are experiencing the pandemic may worsen. This study investigated the contribution of life changes due to the coronavirus to emotional distress in individuals with a diagnosis of chronic central sensitization pain and tested whether the associations between level of pain and sensitization were independent of or mediated by emotional distress. Methods: Spanish individuals with chronic pain ( N  = 362) completed an online survey on direct or indirect exposure to the consequences of COVID‐19, pain intensity, and emotional distress. They also completed central sensitization questionnaires. Results: An association was found between changes in daily routines and pain intensity, emotional distress, and sensitization scores. Correlations were found between emotional distress, sensitization, and pain intensity. Significant predictors of emotional distress were age, difficulty in receiving medical care, changes in daily routines, and diminished social support. Emotional distress did not mediate the association between sensitization and pain intensity. Conclusion: Due to the COVID‐19 situation, individuals with central sensitization pain syndromes may be at higher risk of developing psychological distress. Interdisciplinary interventions involving psychologists are urgently needed to provide this population with appropriate health care.